Optimalisasi Ketepatan Membaca Al-Qur'an dengan Metode Yanbu'a Santri Putri Pondok Pesantren Hidayatul Mubtadiin Sidoharjo Kecamatan Jati Agung Kabupaten Lampung Selatan - Khoirunnisa Khoirunnisa (Departement of Mathematics Education, 2024)
Optimizing the accuracy of reading the Qur'an is one of the important aspects in Islamic education, especially in Islamic boarding schools. This study aims to evaluate the effectiveness of the application of the Yanbu'a method in improving the accuracy of reading the Qur'an among female students at the Hidayatul Mubtadiin Islamic Boarding School, Sidoharjo, Jati Agung District. The Yanbu'a method was chosen because of its systematic and structured approach in teaching tajwid and makhraj letters. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation studies. Observations were conducted to assess the implementation of the Yanbu'a method in the classroom, while interviews with teachers and students provided insight into the experience and effectiveness of the method. Documentation studies were conducted to analyze the development of Qur'an reading skills before and after the application of the method. The results of the study showed that the Yanbu'a method significantly improved the accuracy of reading the Qur'an among female students. The use of this method helps students understand and apply the rules of tajwid better, as well as improve their makhraj letters. The evaluation also revealed that the Yanbu'a method facilitates more structured learning and provides the support needed by students in the learning process. In conclusion, the application of the Yanbu'a method at the Hidayatul Mubtadiin Islamic Boarding School has proven effective in optimizing the accuracy of reading the Qur'an. This study recommends that the Yanbu'a method be applied more widely in other Islamic boarding schools as part of efforts to improve the quality of Qur'an education. In addition, it is important to continue to evaluate and adjust the method to suit the development of the needs of students.